"Research-Based Lesson Study" Workshop for English Teachers: Exploring Inquiry-Based Learning Strategies to Improve Comprehensive Reading Skills - Suparman, Asep; Pratiwi, Ma'rifah Nur; Kartika, Hilda Sry; Munawir, Ahmad Farhi (Indonesian Journal of Community Empowerment (IJCE), 2024)
This community service program aims to strengthen English teachers’ pedagogical competence by implementing a research-based lesson study workshop focusing on inquiry-based learning strategies to improve students’ reading comprehension skills. The workshop was carried out through a cycle of planning, implementation, observation, and reflection involving collaborative participation among teachers. Data were collected through pre-test and post-test, questionnaires, and field observations. The results indicate that teachers gained a deeper understanding of inquiry-based learning and successfully applied it in designing and conducting reading comprehension lessons. Furthermore, the collaborative reflection process enhanced teachers’ professional development and teaching quality. This activity demonstrates that lesson study integrated with inquiry-based strategies is an effective approach to support teacher capacity building and to foster students’ active engagement in learning.